2018
DOI: 10.1002/cbdv.201800070
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic Effects of a Polysaccharide from Tetrastigma hemsleyanum Diels & Gilg in Alloxan‐Induced Diabetic Mice

Abstract: Tetrastigma hemsleyanum Diels & Gilg, a well-known traditional Chinese medicine, possesses antitumor and anti-inflammatory activity, etc. However, the anti-diabetic effect has not been determined. In our present study, a water-soluble polysaccharide, named THP with molecular weight of 93 307 Da, was isolated from T. hemsleyanum by DEAE-52 ion-exchange and Sephadex G-100 chromatography. It contains rhamnose, arabinose, mannose, glucose, and galactose in the molar ratio of 0.07:0.14:0.38:0.21:0.31. Then anti-dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The monosaccharide composition of DPRG was analyzed using an Agilent HP6890 GC with a FID injector (Agilent Technologies, USA) equipped with a HP-5 capillary column (30 m × 0.25 mm) and a flame ionization detector. The temperature program was from 170 °C to 230 °C with a rate of 2 °C/min and at 230 °C for 5 min [39,40,41].…”
Section: Methodsmentioning
confidence: 99%
“…The monosaccharide composition of DPRG was analyzed using an Agilent HP6890 GC with a FID injector (Agilent Technologies, USA) equipped with a HP-5 capillary column (30 m × 0.25 mm) and a flame ionization detector. The temperature program was from 170 °C to 230 °C with a rate of 2 °C/min and at 230 °C for 5 min [39,40,41].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, further study indicated RTP-3-1 was high purity polysaccharide with a molecular weight of 1244.2 kDa, and it is mainly composed of 4 kinds of monosaccharides: arabinose, galacturonic acid, galactose, and fructose, the proportion is 8.39%, 7.18%, 20.70%, and 63.70%, respectively. Ru et al, 2018a , Ru et al, 2018b ) extracted a polysaccharide THP from T. hemsleyanum , with the average molecular weight estimated as 93.307 kDa. The results of study on the composition of polysaccharide showed that it was mainly composed of rhamnose, arabinose, mannose, glucose, galactose with the molar ratio of 0.07:0.14:0.38:0.21:0.31.…”
Section: Chemical Compounds Of Themsleyanummentioning
confidence: 99%
“…Hua Shi Xuan Fei mixture (Approval number of Zhejiang medicine, Z20200026000), which is mainly composed of T. hemsleyanum , has been approved by Zhejiang Provincial Drug Administration for clinical treatment of COVID-19. Futhermore, the modern pharmacological studies had shown that T. hemsleyanum also had effects of anti-inflammatory ( Ji et al, 2019 ), antioxidant ( Hossain et al, 2011 ), antivirus ( Ding et al, 2019 ), antitumor ( Lin et al, 2014 ) antipyretic ( Yang and Wang, 2014 ), anti-hepatic injury ( Ma et al, 2012 ), immunomodulatory ( Xu et al, 2008 ), anti-bacterial ( Chen et al, 2019 ), hypoglycemic ( Ru et al, 2018a , Ru et al, 2018b ) etc. Numerous reports have demonstrated that the biological activities of T. hemsleyanum are attributed to its many chemical components ( Fu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above pharmacological activities, a recent study shows that a water-soluble polysaccharide with a molecular weight of 93307 Da, named THP, is extracted from TDG. THP has exhibited strong hypoglycemic activity in the alloxan induced mouse model, with its treatment being discovered to promote the activity of antioxidant enzymes (GSH-Px, SOD, and CAT) and reduce the content of malondialdehyde (MDA), while THP could restore the structure of pancreas and therefore affect insulin release, as it may be a natural candidate for the treatment of diabetes ( Ru et al., 2018 ). The research team obtained novel of polysaccharide (THDP-3) purified from the stems and leaves of TDG via anion exchange chromatography with a molecular weight of 77.98 kDa.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%